Fleas (Siphonaptera) of Turkey: species composition, geographical distribution and host associations - Keskin, Adem; Hastriter, Michael W.; Beaucournu, Jean-Claude (Zootaxa, 2018)
A list of the fleas species reported from Turkey is provided, with their geographical distribution and host associations. A total of 115 flea taxa (83 species, 32 subspecies) belonging to 36 genera and seven families are listed. The most common families are Ctenophthalmidae (n= 44) and Ceratophyllidae (27), followed by Ischnopsyllidae (13), Leptopsyllidae (11), Pulicidae (11), Vermipsyllidae (5) and Hystrichopsyllidae (4).